2000
DOI: 10.1108/13552550010335976
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship: what triggers it?

Abstract: It is apparent that there exists no such thing as one identifiable and universal entrepreneurial culture. Furthermore, the key to initiating the process of entrepreneurship lies within the individual members of society, and the degree to which a spirit of enterprise exists, or can be stimulated. The key question is, what triggers the release of this invaluable enterprising spirit? This paper seeks to make a small contribution towards an explanation by focusing on one aspect – the relationship of certain cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
1
21

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(148 citation statements)
references
References 4 publications
6
120
1
21
Order By: Relevance
“…To be more specific, Turkish entrepreneurs need market information, technical assistance, information resources and training in finance and marketing to accumulate the resources necessary for expansion. Thus formal education in business or entrepreneurship has been recognized as an influencing factor affecting entrepreneurial growth in developing economies (Dickson et al, 2008;Gibb, 1996;Morrison, 2000). Therefore the objective of this study is to determine the influential factors that can be realized by the farmers in order to enhance their agri-entrepreneurship skills and traits.…”
Section: During the Ninth Malaysia Plan (2005-2009) (Nmp)mentioning
confidence: 99%
See 1 more Smart Citation
“…To be more specific, Turkish entrepreneurs need market information, technical assistance, information resources and training in finance and marketing to accumulate the resources necessary for expansion. Thus formal education in business or entrepreneurship has been recognized as an influencing factor affecting entrepreneurial growth in developing economies (Dickson et al, 2008;Gibb, 1996;Morrison, 2000). Therefore the objective of this study is to determine the influential factors that can be realized by the farmers in order to enhance their agri-entrepreneurship skills and traits.…”
Section: During the Ninth Malaysia Plan (2005-2009) (Nmp)mentioning
confidence: 99%
“…(Morrison, 2000) found that the process of entrepreneurship initiation has its foundations in person and intuition and society and culture. It is much more holistic than simply an economic function and represents a composite of material and immaterial, pragmatism and idealism.…”
Section: During the Ninth Malaysia Plan (2005-2009) (Nmp)mentioning
confidence: 99%
“…Culture factor: Culture is said to play an important role in influencing entrepreneurship (Morrison, 2000). Basing on Hofstede's national cultural dimensions -power distance, uncertainty, avoidance, masculinity/feminity, individualism/collectivism, research has been trying to prove that entrepreneurship intention is favored in cultures with a high degree of individualism, low uncertainty, high power distance and masculinity (Hayton et al, 2002).…”
Section: Determinants Of Entrepreneurship Intentionmentioning
confidence: 99%
“…Brannback et al (2007) highlighted the need for replication in order to advance scientific knowledge in developing economics area. Furthermore, it was claimed that intentions-based models are likely to vary across cultures, economic conditions and there is a need to test current models of entrepreneurial intentions as a means of observing the robustness of current theories and advancing the field of entrepreneurship (Morrison, 2000). In Vietnam, it could be stated that what influences entrepreneurial intentions is still an understudied phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The elements of these relationships include trust, respect, loyalty, common background and experience and shared social contexts (Morton et al, 2006). The literature on small business and entrepreneurship is replete with studies examining the valuable role played by family and friends as a support system of MSMEs (Morrison, 2000;Cooke, 2001;Anderson, Jack & Dodd, 2005;Luo, Zhuo & Liu, 2005;Arinaitwe, 2006). Results of many studies converge on conclusions that family and friends offer insights or examples on how to manage a business based on their own experiences (i.e., role modeling), psycho-emotional and financial support, and referral to other sources of inputs to business operation.…”
Section: Dimensions Of Social Capitalmentioning
confidence: 99%